Pengaruh Capital Intensity, Karakter Eksekutif, dan Kepemilikan Institusional pada Tax Avoidance - Sriartini, Ni Putu Putri; Supadmi, Ni Luh (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
The study aims are to obtain empirical evidences regarding to the effects of capital intensity, executive character, and institutional ownership on tax avoidance at manufacturing companies listed on Indonesia Stock Exchange in 2019-2022. The sample determination used a purposive sampling technique so that a total of 73 companies were obtained with four years of observation or a total of 292 observation data. The data analysis technique using multiple regression test through SPSS software. Based on the result of research, it obtained that capital intensity has negative effects on tax avoidance. This means the higher capital intensity, the lower level of tax avoidance will get, on the other hand executive character and institutional ownership have no effect on tax avoidance.